Growth and Reproductive Performance of American Cockroach (Periplaneta Americana) as Affected by Photoperiod and Feed Type - Obiero, Calvince Ochieng; Ochieng, Calvince; Ojiewo, Chris; Aboge, Danstone (Journal of Entomology and Zoology Studies, 2024)
American cockroach is a reliable source of protein as an animal feed but remains unexploited. Little is known on the right combination of environmental factors for their mass production under artificial conditions. This study assessed the effect of photoperiod and feed as key factors in cockroach rearing on their growth and reproductive performance. Factorial experiment with two factors: photoperiod at four levels; 3L:21D, 6L:18D, 12L:12D, and 18L:6D, and feed at two levels (Chick mash, and chick mash + carrot) was designed. The experiment was laid in a split-plot design with photoperiod as the main plot factor and feed as the sub-plot factor. Measurements were taken on a weekly basis for growth parameters (body mass, body length and cephalic length), and reproductive parameters (length of the ootheca, number of eggs per ootheca and weight of the ootheca) throughout the feeding period. Photoperiod significantly affected the body mass (p<0.000) and cephalic length (p=0.006) of the cockroaches but insignificantly affected their reproductive parameters. Feed type did not have significant effect on both the growth and reproductive performance of the cockroaches. However, photoperiod and feed interaction had significant positive effect on the growth parameters of the cockroaches but insignificantly affected the reproductive parameters. The best photoperiod and feed combination for maximum growth of the cockroaches was 3L: 21D and chick mash. More similar studies targeting other environmental conditions are needed to establish complete set of suitable conditions for mass rearing of cockroaches.
Keywords: Cockroach; Rearing; Feeding; Photoperiod; Growth; Reproduction